Caracterización física y organoléptica de árboles cabezas de clon de genotipos de café robusta de alta productividad para la Provincia de los Ríos - Suarez Prieto, Dennise Xiomara (2016)
SUMMARY The work is developed in the Bank of germplasm of genotypes promising of coffee robust that was installed in the year 2011, in the parish of the Angels, canton Ventanas of the province of Los Rios. The lot was located to a height of 117 meters above sea level, of training ecological "forest dry Tropical" and with temperatures middle of 23 to 26 ° C and rainfall of 1500 to 2000 mm. The objectives of the present study were: determine it influence of them features agroecological of it area crop on them features physical and organoleptic of them clones promising of coffee robust; Identify the distinctive characteristics of grain and Cup, promising clones of robusta coffee of genebank in Los Ríos, and profiling of sturdy promising clones of coffee quality to the area of Los Ríos. Them clones elite of coffee robusta for Ventanas, correspond to the following accessions: CRT-2 pl 2, CRT-20 pl 7, RRS-11 pl 3, CRT-2 pl 17 and JCL-6 pl 2; with levels of productivity potential of 84 to 116 qq of coffee gold / has. With phenotypic characteristics of plant height varying from 2.90 to 3.20 m, with 42 to 66 branches, branch of 100 to 140 cm length, distance 5-7 cm internodes, < 5% fruit openings and an average weight of 1.50 to 2.32 grams per fruit. With regard to their features physical, of drink e industrial is indicate that the features of the grain were of 5.7 mm for size of the grain, density of 734 g/l, performance of coffee toasting of the 83%; of features industrial of 177 ml of extract retrieved, 27% in performance of coffee green and a categorization of 1.5% for solid soluble. Quality of beverage with characteristics of fragrance light cedar, dried fruits, roasted coffee and fruits, cocoa flavors; aroma light to honey of cana; Of body middle and creamy.